Controlling morphology and crystalline structure in poly(3-hexylselenophene) solutions during aging. Issue 130 (21st December 2015) - Wang, Yue; Liu, Xiaofeng; Peng, Juan; Qiu, Feng
Abstract : The crystallization behavior of poly(3-hexylselenophene) in aged solution is investigated and a bundlelike spherulitic morphology is observed, which is so far scarcely observed in polyselenophenes. Abstract : Poly(3-hexylselenophene) (P3HS) is much less studied compared with its close analogue poly(3-hexylthiophene) despite its excellent electronic properties. In this work, we report the crystallization behavior of P3HS in aged solution and the effects of aging time, solution concentration, and solvents on the self-assembly of P3HS are explored. A novel bundlelike spherulitic morphology is observed, which is so far scarcely observed in polyselenophenes. These P3HS spherulites consist of nanoribbons in which the polymer chains adopt a flat-on orientation associated with form II crystals. The formation mechanism and kinetics of P3HS spherulites are discussed in detail. Overall, this work offers an effective way to demonstrate how the P3HS crystallize in solution and the correlation between its morphology and crystalline structure, which improves our understanding of P3HS crystallization and facilitates the ongoing exploration of using such spherulites in organic electronics.